Mozambique Country Water Resources Assistance Strategy : Making Water Work for Sustainable Growth and Poverty Reduction - World Bank (Washington, DC, 2012)
Mozambique's continuous efforts to sustain economic growth and reduce poverty face a number of constraints including its economic and political history, and its geography and climatic conditions. It is widely accepted that future economic growth of the country will continue to rely on its natural resources base and, specifically, on sustainable use of land and water resources. Mozambique has plentiful land and water resources that provide great potential for the production of a variety of crops, livestock development and industrial growth. However, high climate variability resulting in frequent recurrent droughts and floods, limited water resources availability in the most developed southern part of the country, high dependency on international water resources and very limited water management infrastructure result in the economy being highly vulnerable to water shocks and water being a constraint on growth and poverty reduction. The development of Mozambique Country Water Resources Assistance Strategy (CWRAS) was complementary to the Bank Country Partnership Strategy (CPS) process supporting its approach and priorities. It is consistent with the country's development priorities as defined in Second Poverty Reduction Support Strategy (PARPA II) and the sector priorities identified in the national water resources management strategy. The CWRAS' recommendations build upon the Bank's specific strengths vis-a-vis other development donors and, at the same time, are expected to guide the engagement of development partners and promote donor coordination and cooperation in the Mozambique's water resources sector. The main objective of this CWRAS is to assist the Government of Mozambique in prioritizing water resources interventions based on an analysis of Mozambique's changing socio-economic circumstances, and the areas of possible Bank engagement over the next 3-5 years.